EFFECTS OF A PROTOCOL OF ASSISTED DYNAMIC PASSIVE FLEXIBILITY TRAINING IN PARTICIPANT ADULTS OF LABOR GYMNASTICS PROGRAM AT THE BIOMEDICAL SCIENCES COLLEGE OF CACOAL FACIMED (Fiep Bulletin - online, 2013)
The main objective of this research was to analyze and compare the effects of a assisted dynamic flexibility protocol in labor gymnastics at the Biomedical Sciences College of Cacoal-FACIMED, (Rondônia Brasil). The sample was composed by 19 employees from both genres with an average age of 32,2 years ±11,94, divided into 2 groups: Experimental group (EG) (women, n=5 and men, n=4) and the control group (CG) (women, n=5 and men, n=5). All the evaluations were made at the FACIMED`s Physiology and Biomechanics Laboratory from Biomedical Sciences College of Cacoal-FACIMED the 17 to the 20 of March, 2008 (diagnostic evaluation) and from the 23 to the 28 of May, 2008 (post-training evaluation), having the corresponding schedule from 14:00 to 17:00. The pre- and post-tests (which measured the articular amplitude) were applied by using the goniometric method in Thoracic Lumbar Flexion (TLF); Right Hip Flexion (RHF); Left Hip Flexion (LHF); Right Shoulder Horizontal Extension (RSHE) and the Left Shoulder Horizontal Extension (LSHE). The training was executed during six minutes in the labor gymnastics program, two or three times a week in a period of eight weeks, and these employees attended at least 15 sessions, and at most 23 sessions of gymnastics, and a control group was formed to make a comparison possible. Results: Through the statistical analysis by using a Paired-Samples t Test Student, it has been noticed meaningful differences (p
Keywords: Stretching technique; labor gymnastics; flexibility